2015
DOI: 10.1111/eos.12190
|View full text |Cite
|
Sign up to set email alerts
|

Migration of titanium dioxide microparticles and nanoparticles through the body and deposition in the gingiva: an experimental study in rats

Abstract: The aim of this experimental work was to evaluate deposition of titanium dioxide (TiO2 ) microparticles and nanoparticles, which could originate from titanium bioimplants, in the gingiva. Wistar rats were injected intraperitoneally (i.p.) with a suspension of TiO2 particles of different sizes (150, 10, or 5 nm). The rats were killed 12 months post-injection, and the buccal and lingual gingivae were resected and evaluated using light and scanning electron microscopy. Energy-dispersive X-ray spectroscopy (EDS) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 41 publications
1
28
1
Order By: Relevance
“…Hence, it is evident that NP agglomeration size and surface reactivity must be taken into account when considering health matters . In this context, in a previous study on gingival tissue we found that the agglomerates of particles in the micro‐size range did not cause an inflammatory reaction . Similar results were observed in lung and kidney tissue samples in the present study.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Hence, it is evident that NP agglomeration size and surface reactivity must be taken into account when considering health matters . In this context, in a previous study on gingival tissue we found that the agglomerates of particles in the micro‐size range did not cause an inflammatory reaction . Similar results were observed in lung and kidney tissue samples in the present study.…”
Section: Discussioncontrasting
confidence: 54%
“…Specifically, metallic titanium implants are a potential source of release of titanium dioxide (TiO 2 ) microparticles (MPs) and nanoparticles (NPs) into the bioenvironment . It is well known that NPs have a greater surface‐to‐volume ratio than MPs, and are therefore biologically more reactive and potentially more harmful to human health …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with dental implants, their origin has been assumed to be the implants. After injecting male Wistar rats intraperitoneally with a suspension of TiO 2 particles (1.6 g/1,000 g body weight) of different sizes (5 nm, 10 nm, 150 nm), specimens of gingival tissue exhibited agglomerates of nanoparticles, with a predilection on the buccal side (Guglielmotti et al, 2015). In an animal experiment (Schliephake, Reiss, Urban, Neukam, & Guckel, 1993), traces of titanium were found 5 months after implant placement in tissue specimens of lungs, kidneys, and liver.…”
Section: Titanium Particles In the Tissues And Their Originmentioning
confidence: 99%
“…In contrast, a study showed that titanium ions at concentration between 1 and 9 ppm did not affect the viability of osteoblasts, osteoclasts, and gingival epithelial cells . Nanoparticles were described as more biologically reactive and more potentially harmful than microparticles because of their greater surface-tovolume ratio (Guglielmotti et al, 2015). Pettersson et al (2017) showed that titanium particles generate a pro-inflammatory response in macrophages.…”
Section: Bonementioning
confidence: 99%